Green Light Enhances the Postharvest Quality of Lettuce During Cold Storage - Shafieh Salehinia; Fardad Didaran; Yvan Gariepy; Sasan Aliniaeifard; Sarah MacPherson; Mark Lefsrud (Horticulturae)
The postharvest quality of lettuce (Lactuca sativa) is significantly influenced by the lighting environment during storage. This study evaluated the effects of green LEDs at 500 nm and 530 nm, white LEDs (400–700 nm), and dark storage on lettuce quality over 14 days at 5 °C. All treatments were applied at 10 µmol m−2 s−1 under a 12 h photoperiod. Quality parameters measured included moisture loss, relative water content (RWC), photosynthetic rate, chlorophyll content (SPAD), total soluble solids (TSSs), electrolyte leakage (EL), color change (∆E), texture (crispness), and overall visual quality (OVQ). Lettuce stored under green LEDs, particularly 530 nm, exhibited superior postharvest quality. Compared to dark storage, 530 nm reduced moisture loss by 7.1%, increased RWC by 9.2%, and reduced transpiration rate. The green light preserved photosynthetic activity (43% decline vs. 77% in the dark), increased TSS, reduced color change by 42%, improved crispness by 46.1%, and limited EL to 54.5%. Shelf life was extended by approximately four days. The 500 nm treatment showed notable improvements, including an 8.4% reduction in moisture loss, 8.2% higher RWC, a smaller photosynthesis decline (25%), and the lowest EL (53.1%). It improved color retention (∆E reduced by 45.3%) and crispness (46.8%). Both green wavelengths effectively maintained lettuce quality during cold storage, with 530 nm being the most effective overall. These results suggest that targeted green LED lighting is a promising, energy-efficient strategy to preserve postharvest quality and extend shelf life in leafy greens.